Ganong's review of medical physiology - Kim E. Barrett (McGraw-Hill Medical, 2019)
For more than four decades, Ganong’s Review of Medical Physiology has been helping those in the medical field understand human and mammalian physiology. Applauded for its interesting and engagingly written style, Ganong’s concisely covers every important topic without sacrificing depth or readability, and delivers more detailed, high-yield information per page than any other similar text or review. Thoroughly updated to reflect the latest research and developments in important areas such as chronic pain, reproductive physiology, and acid-base homeostasis, Ganong’s Review of Medical Physiology, Twenty-Sixth Edition incorporates examples from clinical medicine to illustrate important physiologic concepts. Ganong's will prove valuable to students who need a concise review for the USMLE, or physicians who want to keep pace with the ever-changing world of medical physiology